Not the same thing: metastatic PTCs have a different background than ATCs - Dario de Biase; Federica Torricelli; Moira Ragazzi; Benedetta Donati; Elisabetta Kuhn; Michela Visani; Giorgia Acquaviva; Annalisa Pession; Giovanni Tallini; Simonetta Piana; Alessia Ciarrocchi (Endocrine Connections, 2018)
Anaplastic thyroid cancer (ATC) is a rare but highly aggressive form of thyroid cancer. By contrast, differentiated papillary thyroid cancer (PTC) only rarely behave aggressively and develop distant metastasis. Whether distantly metastatic PTC (DM-PTC) and ATC share a common genetic background is still to be defined. We used next-generation sequencing (NGS) to explore the genetic background of a cohort of ATC and DM-PTC and a group of well-differentiated PTCs that did not developed distant metastasis as control (ctrl-PTC). A panel of 128 amplicons within 21 thyroid cancer-related genes was analyzed in a set of 151 thyroid cancer samples including 66 ATCs and DM-PTCs. We showed that the ATC/DM-PTC group had an overall mutational load higher than ctrl-PTCs and that ATCs and DM-PTCs are characterized by a different genetic background, with the exception of mutations in the TERT promoter that were overrepresented in both ATCs (61.1%) and DM-PTCs (48.2%) vs non-aggressive ctrl-PTCs (7.6%). In ATCs, TERT promoter mutations were frequently associated with TP53 mutations, while in the DM-PTCs no significant co-occurrence was observed. No significant association of MED12 mutations with aggressiveness of thyroid cancer was observed in our analysis. Finally, correlation analysis showed that increasing number of mutations negatively impact on patient overall survival also within the ATC and DM-PTC group. In conclusions, overall our analysis further highlights the relevance of TERT promoter mutations in driving aggressiveness and provides new pieces of information in the definition of aggressiveness evolution of thyroid cancer lesions.